Two-way plant mediated interactions between root-associated microbes and insects: from ecology to mechanisms - Pangesti, Nurmi; Pineda, Ana; Pieterse, Corné M.; Dicke, Marcel; Van Loon, Joop J. (Frontiers in Plant Science, 2013)
Plants are members of complex communities and function as a link between above- and below-ground organisms. Associations between plants and soil-borne microbes commonly occur and have often been found beneficial for plant fitness. Root-associated microbes may trigger physiological changes in the host plant that influence interactions between plants and aboveground insects at several trophic levels. Aboveground, plants are under continuous attack by insect herbivores and mount multiple responses that also have systemic effects on belowground microbes. Until recently, both ecological and mechanistic studies have mostly focused on exploring these below- and above-ground interactions using simplified systems involving both single microbe and herbivore species, which is far from the naturally occurring interactions. Increasing the complexity of the systems studied is required to increase our understanding of microbe - plant - insect interactions and to gain more benefit from the use of non-pathogenic microbes in agriculture. In this review, we explore how colonization by either single non-pathogenic microbe species or a community of such microbes belowground affects plant growth and defense and how this affects the interactions of plants with aboveground insects at different trophic levels. Moreover, we review how plant responses to foliar herbivory by insects belonging to different feeding guilds affect interactions of plants with non-pathogenic soil-borne microbes. The role of phytohormones in coordinating plant growth, plant defenses against foliar herbivores while simultaneously establishing associations with non-pathogenic soil microbes is discussed.